Education for citizenship in contexts of diversity in the metropolitan area of Lisbon - Hortas, Maria João (2019)
Education for citizenship in contexts of diversity arises from the intensification and diversification of migratory flows to Portugal, in particular to the Lisbon Metropolitan Area, in the transition from the twentieth century to the twenty-first century. The arrival of people from diverse origins to the city is visible in the areas of settlement not only in the multitude of uses, practices and forms of appropriation of space but also in the dynamics unfolded among the recently arrived citizens, the local population and the existing community institutions. The schools of the neighbourhoods hosting this diversity of residents have registered remarkable changes in their students and the integration of sociocultural diversity is today one of the main challenges faced by the educational community. School is essential in the construction of this plural society. It is responsible for training people and promoting their citizenship. In the context of diversity, the school can help students to develop their identity with the cultural group they belong to and to transmit values of global citizenship and training people for a ‘multicultural citizenship’. In this article, we pay special attention to the role of the school and family in the construction of citizenship in young people from different cultures, basing this on the empirical data gathered from: children and young people, both with native and with immigrant backgrounds attending public schools in the Lisbon Metropolitan Area; their respective families; and the school projects. Combining the perceptions of students’ practices, families’ expectations and school policies, we identify and analyse the multiple dimensions that education for citizenship can assume in a diverse educational context.